A Pilot Study of Two Different Constraint-Induced Movement Therapy Interventions in Children With Hemiplegic Cerebral Palsy After Botulinum Toxin Injection During Preschool Education - Wu, Chin-Lung; Liao, Su-Fen; Liu, Chi-Hsin; Hsieh, Yu-Ting; Lin, Yi-Ru (Frontiers in Pediatrics, 2020)
Introduction: To establish a pilot study on applying 2 low dose (40 hours) constraint-induced movement therapy(CIMT) interventions in children with hemiplegic cerebral palsy(CP) after botulinum toxin(BoNT-A) injection during preschool education. Methods: Five children with spastic CP (mean age:5.31 years; Gross Motor Function Classification System level I and II) under regular BoNT-A injections and rehabilitation program were included. Participants were randomly allocated to 1 of 2 CIMT programs (40 hours): a 2-week 4-hours/day CIMT program and a 4-week 2-hours/day CIMT program. One CIMT program was performed 1 month after a BoNT-A injection, and then the second program was implemented with the next injection. The outcomes were measured by changes in Goal Attainment Scaling(GAS), the grasp and Visual-Motor Integration(VMI) test in Peabody-Developmental Motor Scales(PDMS), self-care scale on the Functional Skill Scale and the Caregiver Assistance in Chinese Version of Pediatric Evaluation of Disability Inventory(PEDI-C), Anxiety and Oppositional Defiance Problems of Achenbach System of Empirically-Based Assessment before and after the CIMT interventions, and at every 2 months’ follow-up thereafter. Results: The mean age of the participants was 5.31 years, BMI was 16.7 (kg/m2), VIQ was 86.4 ± 8.5 and dose of BoNT-A injection in the upper limb was 42 ± 26.6 units. Grasp, VMI and self-care on the Functional Skill Scale were significantly better in the 4-week 2-hours/day CIMT program(p<0.001,p=0.001,p<0.001). GAS, grasp, VMI and 2 self-care scales of PEDI were significantly improved after the CIMT program, and improvement continued for up to 4 months after the program. There was no clinical evidence in the scores for anxiety and oppositional defiance problems during the study period. Conclusions: The preliminary findings, although limited, also suggest a potential therapeutic role for the school-based CIMT program after BoNT-A injection. The 4-week 2-hours/day CIMT program might be better than a 2-week 4-hours/day program in terms of self-care and hand function when performed in kindergarten in this pilot study. Furthermore, this pilot study provides valuable information; therefore, it is crucial to include more CP children and blinded assessor for hand function and ADL in the future study.